Herbal Extract-Induced DNA Damage, Apoptosis, and Antioxidant Effects of C. elegans: A Comparative Study of Mentha longifolia, Scrophularia orientalis, and Echium biebersteinii - Anna Hu; Qinghao Meng; Robert P. Borris; Hyun-Min Kim (Pharmaceuticals)
Background: Herbal medicine represents a rich yet complex source of bioactive compounds, offering both therapeutic potential and toxicological risks. Methods: In this study, we systematically evaluated the biological effects of three traditional herbal extracts—Mentha longifolia, Scrophularia orientalis, and Echium biebersteinii—using Caenorhabditis elegans as an in vivo model. Results: All three extracts significantly reduced worm survival, induced larval arrest, and triggered a high incidence of males (HIM) phenotypes, indicative of mitotic failure and meiotic chromosome missegregation. Detailed analysis of germline architecture revealed extract-specific abnormalities, including nuclear disorganization, ectopic crescent-shaped nuclei, altered meiotic progression, and reduced bivalent formation. These defects were accompanied by activation of the DNA damage response, as evidenced by upregulation of checkpoint genes (atm-1, atl-1), increased pCHK-1 foci, and elevated germline apoptosis. LC-MS profiling identified 21 major compounds across the extracts, with four compounds—thymol, carvyl acetate, luteolin-7-O-rutinoside, and menthyl acetate—shared by all three herbs. Among them, thymol and carvyl acetate significantly upregulated DNA damage checkpoint genes and promoted apoptosis, whereas thymol and luteolin-7-O-rutinoside contributed to antioxidant activity. Notably, S. orientalis and E. biebersteinii shared 11 of 14 major constituents (79%), correlating with their similar phenotypic outcomes, while M. longifolia exhibited a more distinct chemical profile, possessing seven unique compounds. Conclusions: These findings highlight the complex biological effects of traditional herbal extracts, demonstrating that both beneficial and harmful outcomes can arise from specific phytochemicals within a mixture. By deconstructing these extracts into their active components, such as thymol, carvyl acetate, and luteolin-7-O-rutinoside, we gain critical insight into the mechanisms driving reproductive toxicity and antioxidant activity. This approach underscores the importance of component-level analysis for accurately assessing the therapeutic value and safety profile of medicinal plants, particularly those used in foods and dietary supplements.